The impact of soil and moisture on nitrogen mineralisation rates in biosolids - Pritchard, Deborah; Rigby, Hannah (Australian Water Association, 2010)
Nitrogen (N) based loading rates are commonly used to determine land application rates of biosolids, calculated to best target the agronomic N needs of the crop. The rate of N mineralisation following the amendment of soils with biosolids over a range of specific environmental conditions needs to be accurately quantified to prevent overloading the soil with N in excess of plant uptake. The N release characteristics of anaerobically digested dewatered biosolids cake (DBC), lime-amended biosolids (LAB) and alum sludge (AS), in comparison to urea as a source of readily available N, were investigated in a soil incubation study. The experimental design included two soil types and three moisture regimes (25%, 50% and 100% gravimetric water holding capacity (GWHC)). There was no significant effect of soil type on the proportion or rate of N mineralisation. Nitrogen mineralisation rate was greater for LAB and AS compared with DBC and lime amended biosolids which had been stockpiled (LABs) for 12 months.The rate of N mineralisation was also dependent on moisture and was generally greater at 50% GWHC compared to 25% GWHC, but at 100% GWHC losses of N were observed, especially from soil amended with LAB; this is attributed to denitrification. The proportion of mineralisable N (% organic N) at 50% GWHC was greater for LAB (72%) and AS (64%) in comparison with DBC (32%) and LABs (26%). These results are consistent with previous findings and demonstrate that the organic matter content of LAB and AS is of a lower stability than DBC and LABs. Plant available N in the first season following the land application of biosolids may be greater than current estimates of 20% and hence N mineralisation, volatilisation rate and denitrification losses for specific products under a range of environmental conditions needs further investigation.